Nicotinamide riboside supplementation corrects deficits in oxytocin, sociability and anxiety of CD157 mutants in a mouse model of autism spectrum disorder - Maria Gerasimenko (Nature Portfolio, 2020)
Abstract Oxytocin (OT) is a critical molecule for social recognition and memory that mediates social and emotional behaviours. In addition, OT acts as an anxiolytic factor and is released during stress. Based on the activity of CD38 as an enzyme that produces the calcium-mobilizing second messenger cyclic ADP-ribose (cADPR), CD157, a sister protein of CD38, has been considered a candidate mediator for the production and release of OT and its social engagement and anti-anxiety functions. However, the limited expression of CD157 in the adult mouse brain undermined confidence that CD157 is an authentic and/or actionable molecular participant in OT-dependent social behaviour. Here, we show that CD157 knockout mice have low levels of circulating OT in cerebrospinal fluid, which can be corrected by the oral administration of nicotinamide riboside, a recently discovered vitamin precursor of nicotinamide adenine dinucleotide (NAD). NAD is the substrate for the CD157- and CD38-dependent production of cADPR. Nicotinamide riboside corrects social deficits and fearful and anxiety-like behaviours in CD157 knockout males. These results suggest that elevating NAD levels with nicotinamide riboside may allow animals with cADPR- and OT-forming deficits to overcome these deficits and function more normally.